Fiscal loss as a tax planning strategy in Indonesia - Putra, Arie Anggara; Saputra, Bambang; Pahala, Indra; Wahono, Puji (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze tax planning strategies related to fiscal losses and business closure within the framework of Indonesian taxation law. Fiscal loss, if not properly managed, can lead to suboptimal tax positions for corporate taxpayers, particularly in the context of business termination or restructuring. Through a normative juridical approach combined with case-based analysis, this paper examines several strategic alternatives, including the revaluation of fixed assets to align book and tax values, corporate mergers as a means to utilize carried-forward fiscal losses, and the procedures for Taxpayer Identification Number (NPWP) and Taxable Entrepreneur Confirmation Number (NPPKP) deregistration. These methods are evaluated in terms of their legal basis, practical implementation, and potential tax efficiency outcomes. The findings suggest that with appropriate planning and compliance, taxpayers can mitigate fiscal burdens, optimize the use of past losses, and ensure a lawful and efficient exit from business operations. The study contributes to the understanding of tax planning as a crucial component of corporate financial strategy, particularly in scenarios involving financial distress or liquidation.